Transformations of (0,1] preserving tails of Δμ-representation of numbers - Isaieva, T.M.; Pratsiovytyi, M.V. (Algebra and Discrete Mathematics, 2016)
In the paper, classes of continuous strictly increasing functions preserving ``tails'' of Δμ-representation of numbers are constructed. Using these functions we construct also continuous transformations of (0,1]. We prove that the set of all such transformations is infinite and forms non-commutative group together with an composition operation.